Specificity of Building Customer Journey Map in Marketing Practices ("Journal "U". Economy. Management. Finance.", 2021)
This article examines the specifics of building a Customer Journey Map, as well as its necessity for enterprises in the modern world in order to better understand their customers, analyze the target audience and conduct effective competition in the Internet environment.
Keywords: marketing; strategy; digital strategy; Customer Journey Map; CJM; infographics; information technology; promotion